Research and Development, Inovasi, dan Pertumbuhan Ekonomi: Studi pada Negara Asia Terpilih - Nurul Inayah; Fransiscus Xaverius Sugiyanto (Universitas Diponegoro, 2023)
In the modern economy, innovation is the main source of increasing productivity, economic growth, and social welfare. Furthermore, innovation is regarded as one of the drivers of economic growth besides the traditional production factors, such as capital and labor accumulation. Research and Development (R&D) funding is one of the strategies for fostering innovation. This study aims to analyze the effects of R&D and innovation on economic growth in 6 Selected Asian Countries during the period 2009-2017. This study used Gross Domestic Product (GDP) per capita as the dependent variable which describes economic growth. Meanwhile, R&D expenditures, patents, labor force participation rate, gross net enrollment in tertiary education, and foreign direct investment are independent variables. In addition, this study was descriptive quantitative research using panel data analysis. The result of this study shows that R&D expenditures, patent, and labor force participation have a positive and significant effect on economic growth in the 6 selected Asian countries. Thus, these results show that there is a significant effect of the innovation variable on economic growth in the 6 selected Asian countries.